The Effect of Religiosity on Life Satisfaction Among Students in the Faculty of Teacher Training - Fauziah Nasution; Nurussakinah Daulay; Masganti Sitorus (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Despite the widespread Islamization in Indonesia, a corresponding increase in life satisfaction among its population has not been clearly observed. This study investigates the impact of religiosity on life satisfaction among students in the Faculty of Teacher Training at the Islamic State University of North Sumatra. Employing a quantitative, cross-sectional design, the research was conducted between October and November 2023. The study population comprised 7.801 students, from which a sample of 380 was selected. The primary variables examined were religiosity (independent variable) and life satisfaction (dependent variable). Data were analyzed using both univariate and multivariate methods: descriptive statistics for univariate analysis and linear regression for multivariate analysis. All statistical procedures were performed using JASP software, version 17. Findings indicate that religiosity significantly influences life satisfaction among students in the Islamic education faculty (p < 0.001). Students with high levels of religiosity were found to be 6.730 times more likely to report greater life satisfaction. These results suggest that religiosity is a strong predictor of life satisfaction and that the regression model provides a robust explanation of the observed data. Nonetheless, the model may not capture all contributing factors, and future research should explore additional variables that may affect life satisfaction. Keyword: Islamization, Life Satisfaction, Religiosity, Students